Cak numerals - Keisuke, Huziwara (Dhaka University Journal of Linguistics, 2009)
Cak is a Luish language of the Tibeto-Burman language family and it is spoken mainly in the Naikhyongchari subdistrict of Bandarban district, Chittagong Hill Tracts (henceforth, CHT),Bangladesh. In this paper, I briefly describe the Cak numeral system. Numerals in Cak are basically nouns. Cak has two series of cardinal numerals: one is the native Cak numerals and the other is borrowed from Marma. The difference between these two types of numerals is reflected in the classifiers that they take: Cak numerals take native Cak classifiers whereas the numerals borrowed from Marma take classifiers of Marma origin. The native Cak numeral for ‘one' is unique in two respects. First, it changes form according to its phonological environment. Second, it appears after classifiers, while the other numerals precede classifiers. Finally, I show that all the ordinal numerals are borrowed from Pali through Marma. Key words: Cak, Marma, numerals, numeral classifiers, Tibeto-Burman languages DOI: 10.3329/dujl.v1i2.3714 The Dhaka University Journal of Linguistics: Vol. 1 No.2 August, 2008 Page: 1-10